Commercial Screen-Printed Electrodes Based on Carbon Nanomaterials for a Fast and Cost-Effective Voltammetric Determination of Paracetamol, Ibuprofen and Caffeine in Water Samples - Núria Serrano (Sensors, 2019)
Carbon screen-printed electrode (SPCE), multi-walled carbon nanotubes modified screen-printed electrode (SPCNTE), carbon nanofibers modified screen-printed electrode (SPCNFE), and graphene modified screen-printed electrode (SPGPHE) were in a pioneer way tested as sensors for the simultaneous determination of the two most consumed pain-killers, paracetamol (PA) and ibuprofen (IB), and the stimulant caffeine (CF) in water by differential pulse voltammetry (DPV). Their analytical performances were compared, and the resulting sensitivities (2.50, 0.074, and 0.24 μA V mg−1 L for PA, IB, and CF, respectively), detection limits (0.03, 0.6, and 0.05 mg L−1 for PA, IB, and CF, respectively) and quantification limits (0.09, 2.2, and 0.2 mg L−1 for PA, IB, and CF, respectively) suggested that the SPCNFE was the most suitable carbon-based electrode for the voltammetric determination of the selected analytes in water at trace levels. The methodology was validated using both spiked tap water and hospital wastewater samples. The results were compared to those achieved by liquid chromatography–tandem mass spectrometry (LC-MS/MS), the technique of choice for the determination of the target analytes.